2022
DOI: 10.1111/infa.12451
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous movements, motor milestones, and temperament of preterm‐born infants: Associations with mother–infant attunement

Abstract: Preterm-born infants and their mothers are at higher risk of showing less attuned interactions. We sought to identify characteristics of preterm-born infants associated with the attunement of mother-infant interactions at the corrected ages of 3-4 months, looking specifically at motor behaviors. We focused on infants' spontaneous movements, achievement of motor milestones, and temperament, which at this young age is often manifested via movement. Sixty preterm-born infants (Mdn gestation age in weeks = 33, 57.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…The quality of such interactions, largely determined by how sensitive parents are and the capacity to coordinate their behavior to the infant’s needs, henceforth attunement, contributes to a myriad of developmental outcomes that span from physical to social cognitive and emotional areas ( van der Voort et al, 2014 ; Vacaru et al, 2019 , 2020 , 2022 ). Attunement entails reciprocal behaviors of the mother and her infant, comprising maternal sensitive behaviors such as attention to infant’s cues, correct and timely interpretation and appropriate responsiveness ( Bornstein and Manian, 2013 ; Lev-Enacab et al, 2022 ). It has been shown that mother’s attunement fosters infant’s developing abilities to share their inner states, and to later achieve intersubjectivity and better communication skills ( Stern et al, 1985 ; Užgiris, 1991 ; Nicely et al, 1999 ), and joint engagement ( Legerstee et al, 2007 ; Rollins and Greenwald, 2013 ).…”
Section: Attunement In Early Social Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of such interactions, largely determined by how sensitive parents are and the capacity to coordinate their behavior to the infant’s needs, henceforth attunement, contributes to a myriad of developmental outcomes that span from physical to social cognitive and emotional areas ( van der Voort et al, 2014 ; Vacaru et al, 2019 , 2020 , 2022 ). Attunement entails reciprocal behaviors of the mother and her infant, comprising maternal sensitive behaviors such as attention to infant’s cues, correct and timely interpretation and appropriate responsiveness ( Bornstein and Manian, 2013 ; Lev-Enacab et al, 2022 ). It has been shown that mother’s attunement fosters infant’s developing abilities to share their inner states, and to later achieve intersubjectivity and better communication skills ( Stern et al, 1985 ; Užgiris, 1991 ; Nicely et al, 1999 ), and joint engagement ( Legerstee et al, 2007 ; Rollins and Greenwald, 2013 ).…”
Section: Attunement In Early Social Interactionsmentioning
confidence: 99%
“…To assess dyadic attunement in mother–infant interactions, it is crucial to identify the behaviors that are typically displayed by infants. These behaviors can vary according to the infant’s temperament and/or context and it has been shown that parents can attune to their infant’s spontaneous movements from an early age ( Lev-Enacab et al, 2022 ). Parental attunement to their infants’ behaviors is marked by sensitive responding to the infant’s cues (i.e., mirroring and emotional availability).…”
Section: Assessing Attunement In Mother–infant Interactionsmentioning
confidence: 99%